2001
DOI: 10.1046/j.1471-4159.2001.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic benzodiazepine treatment of cells expressing recombinant GABAA receptors uncouples allosteric binding: studies on possible mechanisms

Abstract: Functional and behavioral tolerance to chronic benzodiazepine (BZ) exposure has been associated with an uncoupling of the BZ and GABA binding sites. As in rats exposed to BZ for periods of a week or longer, recombinant GABA A receptors (GABARs) expressed in Sf9 cells lose the normally observed allosteric enhancement of [ 3 H]¯unitrazepam binding by GABA agonists, which is measured in homogenized membranes after a few hours exposure to pharmacological doses of agonist BZ. Treatment of Sf9 cells expressing recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 36 publications
(56 reference statements)
1
41
0
3
Order By: Relevance
“…However, phosphorylation (protein kinase C)-dependent subunit-selective receptor endocytosis and/or recycling may be involved (Ali and Olsen, 2001;Kumar et al, 2003;Kittler et al, 2005). GABA A R assembly may be partly based on subunit availability, especially in the unnatural environment of recombinant expression in heterologous cells; however, distinct assembly signals in certain subunits appear to drive formation of preferred receptor subunit compositions (Bollan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phosphorylation (protein kinase C)-dependent subunit-selective receptor endocytosis and/or recycling may be involved (Ali and Olsen, 2001;Kumar et al, 2003;Kittler et al, 2005). GABA A R assembly may be partly based on subunit availability, especially in the unnatural environment of recombinant expression in heterologous cells; however, distinct assembly signals in certain subunits appear to drive formation of preferred receptor subunit compositions (Bollan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, selective endocytosis and/or recycling of receptors based on subunit composition and sensitivity to protein kinase C phosphorylation may be involved (Ali and Olsen, 2001;Kumar et al, 2003;Kittler et al, 2005). We hypothesized that the rapid development of tolerance to acute EtOH potentiation of the tonic current in CA1 neurons may be attributable to the internalization of the ␣4␤␦ extrasynaptic GABA A Rs, which are sensitive to low [EtOH] (SundstromPoromaa et al, 2002;Wallner et al, 2003).…”
Section: Altered Cell-surface and Intracellular Levels Of Gaba A R Sumentioning
confidence: 99%
“…Several published work support the hypothesis that selective changes in the expression of different α subunits is associated with BZ tolerance (Ali and Olsen, 2001;Bateson, 2002, Costa et al, 2002Wafford, 2005); however the role of specific subunits in the mechanism of BZ tolerance development is still not clear. Using knock-in mice in which the α1-, α2-, α3-or α5-GABA A receptor subunits were rendered insensitive to diazepam by histidine-arginine point mutation, van Rijnsoever et al (2004) demonstrated that simultaneous and long-term activation of both α1 and α5 GABA A receptor subunit by diazepam is necessary for the development of tolerance to its sedative action.…”
Section: Introductionmentioning
confidence: 93%
“…The exact molecular mechanism(s) leading to functional uncoupling between GABA and benzodiazepine binding sites remain unknown. Although uncoupling of the benzodiazepine and GABA binding sites could be produced by drugs inhibiting protein kinase A, it is supposed that direct phosphorylation of GABA A receptors is not involved in coupling/ uncoupling processes [26] . The same authors proposed that prolonged benzodiazepine treatment induces internalization of surface GABA A receptors into intracellular vesicles, where the potentiation by GABA is impaired but the normal benzodiazepine binding can occur.…”
Section: Wwwchinapharcom Vlainić J Et Almentioning
confidence: 99%
“…However, long-term administration of non-selective full positive allosteric modulator of GABA action at GABA A receptors leads to alterations in receptor expression and/or function, resulting in the development of tolerance and dependence. Many authors working either on animals [29] , neuronal cultures [30][31][32] or recombinant receptors [13,14,20,25,26,33,34] have found reduced allosteric linkage between GABA and benzodiazepine binding sites as a result of prolonged benzodiazepine action. Moreover, animals and humans treated for prolonged period of time with drugs acting as full positive modulators of GABA action at GABA A receptors developed tolerance characterized by a decreased ability of the drug to produce its pharmacological effect.…”
Section: Wwwchinapharcom Vlainić J Et Almentioning
confidence: 99%